The book of rock stars : 24 musical icons that shine through history - Krull, Kathleen; Alcorn, Stephen (New York : Hyperion Books for Children, 2003)
An illustrated collection of twenty mini-biographies of such rock music legends as Jimi Hendrix, Janis Joplin, Bruce Springsteen, and Carlos Santana.
Includes bibliographical references : (p. [46-48]).
Keywords: Rock musicians -- Biography -- Juvenile literature; Musicians; Rock music